Implementasi Monitoring Website Pemkot Cimahi Menggunakan Uptime Kuma Berbasis VPS - Gilang Trifebriyanto, Fajar; Syani, Mamay; Alpiyasin, Feri; Laia, Firdaus; Parga Zen, Bita (Jurnal Sistem Informasi Galuh, 2026)
The Department of Communication and Informatics (Diskominfo) of Cimahi City manages various digital public services that require high availability. However, the manual monitoring process of these websites is inefficient and prone to delays in detecting downtime. This study aims to implement an automated monitoring system using Uptime Kuma hosted on a Virtual Private Server (VPS) and integrated with a Telegram Bot for real-time notifications. The research method involves configuring Uptime Kuma to monitor 25 government websites via HTTP/HTTPS protocols with a 60-second check interval. The results demonstrate that the system successfully visualizes the status of all websites on a centralized dashboard. Furthermore, the Telegram integration provides instant alerts to the technical team when disruptions occur, significantly reducing the response time and ensuring the reliability of the Electronic-Based Government System (SPBE).